A conceptual framework of control, learn, and knowledge for computer power management - Candrawati, Ria; Hashim, Laili; Mahmuddin, Massudi; Hamzah, Hammuzamer Irwan (2014)
This conceptual paper observes the human inactivity in computer power management and discovers that; the efficiency of the computer power management (CPM)can be achieved by the eligibility of the human inactivity period. This period reduces the efficiency of CPM. This study examines the self-adaptation(SA) and the knowledge repository (KR)concepts, to model the framework of a new approach in computer power management. The essential elements and features from theseconceptswere adapted and applied as a techniqueto a new implementation of CLK-CPM. As a result, this study has proposed a modelof thetheoretical framework and demonstratesit through its conceptual framework for the technique.